(untitled) (Journal of Asian Development Studies, 2024)
This study explores the impact of caste-based discrimination on the educational opportunities of youth in rural areas of Jhelum District, Pakistan. The research seeks to investigate the extent of caste-based differences, examine the education status and opportunities of marginalized castes, explore how caste influences access to educational opportunities, and examine the influence of caste-based discrimination on educational aspirations and choices. The research uses a qualitative approach. Caste-based discrimination in rural areas of Pakistan hinders educational opportunities for youth. This study examines the extent of caste-based differences and their impact on education access and aspirations. It affects education opportunities for youth. This study investigates the issue and its impact on access, aspirations, and educational outcomes. The findings of this study will contribute to a better understanding of the complex issue of caste-based discrimination in education and provide insights for policymakers to develop effective policies that promote equity and inclusivity in educational opportunities for all.